Evaluation of Creole avocados in Nuevo León, Mexico: southern region - Acosta Díaz, Efraín; Hernández Torres, Ismael; Almeyda León, Isidro Humberto (Revista Mexicana de Ciencias Agrícolas, 2018)
The State of Nuevo León, Mexico, is a part of the birthplace of the Mexican breed of avocado (Persea americana Mill. var. drymifolia), where Creole varieties are planted in commercial gardens and backyards, with the outstanding use of the variety Plátano Grueso-1 (local variety). This variety is characterized by an early cycle of physiological maturity, allowing production to concentrate into a relatively short period. The objective of this research was to characterize a group of Creole varieties of avocado in the south of Nuevo León, using morphological characteristics of the fruit. Twenty nine varieties were used including the variety Plátano Grueso-1 (local variety), present in six commercial gardens and a backyard in the municipalities of Aramberri and Zaragoza, Nuevo León. Seventeen materials were identified as having morphological characteristics similar to the variety Plátano Grueso-1, and they were classified into three groups. The first group is formed by 12 varieties with fruit characteristics similar to those of Plátano Grueso-1, with a period of early physiological maturity. The second group is composed of three varieties with characteristics similar to those of Plátano Grueso-1, with an intermediate period of physiological maturity. The third group consists of two varieties with similar fruit characteristics to the variety Plátano Grueso-1, with a late period of physiological maturity. Results suggest that there is a wide variation in the creoles of avocado materials grown in the southern area of the State of Nuevo León, which is an alternative for the diversification of the production and to no longer depend almost exclusively on the variety Plátano Grueso-1.
Keywords: Persea americana Mill.; morphological characterization; genetic resources; Creole varieties